Understanding of ‘Equality, Justice and Equity’ among First Year Undergraduate Students of BPKIHS - Sharma, Sumit; Shakya, D R; Adhikari, S; Chetri, V A; Singh, R R (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Understanding of ‘Equality, Justice and Equity’ at the beginning of medical education will have a great bearing in future career. Objectives: To assess understanding of ‘Equality, Justice and Equity’ among the first year undergraduate students of BPKIHS who were in the beginning of health science/ medical education Methods: This is an academic institute based study carried out among the first year undergraduate students (BSc.- Nursing, BSc.- Allied, BDS and MBBS) of BPKIHS, based on convenient sampling. This included the responses of 181 subjects giving written informed consent. The ‘semi-structured proforma’ and the pretested ‘Bioethics Awareness, Knowledge and Attitude’ questionnaire were used to collect the responses. Results: We had 55% female subjects, more from urban settings (65%). Many students were aware about Bioethics and willing to be a part of Bioethics group. Half of the participants felt the need to discuss their patients’ information with their colleagues. More of them (38%) were not sure not about charging more for service on the rich to compensate for the poor while one fifth (22%) favored and one fifth (20%) disagreed. Most of the participants believed that patient’s wishes should always be adhered to. A few respondent students (4%) also believed that doctors and nurses should refuse to treat violent patients. Majority of the participants had heard of taking informed consent and agreed unentertaining patient’s questions during their posting. Conclusion: There should be various modes of enhancing the teaching learning opportunities for the medical students to learn about ethics and ethical principles including ‘Equality, Justice and Equity ‘and to enhance their positive view.